Agile Project Management: A Communicational Workflow Proposal - Loiro, Carina (2020)
Embracing agility brings change to companies and everyone involved, so people have a fundamental role in project development. It is essential that teams have a good communication, motivation and concern about quality and client satisfaction, Agile Manufacturing is using Agile Project Management to provide the right team to performance difficult tasks and achieve goals. This paper proposes a team that deals with Agile Project Management, named as AGILE team, composed by a product owner, a team leader and team members, and a communication workflow proposal concerning the conjunction of 3 momentums (requirements analyze, planning and design) along the Agile Project Management. The proposed model is being implemented in a lightening manufacturing company in a very early stage.